×

jade_chung

第三題同第四題

Help plzz

附加文件

解答 0

  • eric
    2020-07-23 16:05:10
    3b. =3(n+4)-3n
  • 解數雜貨店
    2020-07-24 09:41:44
    4a) a - 4b = 6 + 2b a = 6(b+1) 4b) To dealt with this kind of question, you have to convert the description into equation. It asked for the change of a, so we would better assume △a as the unknown. △a could be positive or negative to represent increment or decrement repectively. We start with the relation between a and b, a = 6(b+1) After b is decreased by 2, LHS becomes a+△a RHS becomes 6((b-2)+1) Equate both sides gives a+△a = 6(b-1) 6(b+1)+△a = 6(b-1) [∵ a=6(b+1)] △a = 6(b-1) - 6(b+1) △a = -12 So, a is decreases by 12
請填寫內容
解答內容包含禁止的詞
請輸入你的答案
上載文件更改 ×
檔案過大
不支援此檔案
jpg, gif, png, doc, docx, pdf, xls, mov, mp4, m4a, mp3 (檔案上限為50M)